Assessment for acceptance of accounting, marketing and office technology management software applications for instructional delivery among business education lecturers in North-east Nigerian Universities - Hayatu, Suleiman (Kashere Journal of Education, 2023)
This study aimed at assessing the acceptance of accounting, marketing and office technology management software applications for instructional delivery among business education lecturers in universities in North-eastern region of Nigeria. The study adopted descriptive survey design. The study used the constructs of the theory of planned behaviour. The population of the study comprises of 50 business education lecturers in the three universities that offer business education programme which are; Abubakar Tafawa Balewa University Bauchi, Modibbo Adama University Yola and University of Maiduguri. The entire population was used for the study. The instrument for data collection was a structured questionnaire. The instrument was validated by two experts from the department of vocational education, Modibbo Adama university, Yola. The reliability test of the instrument was conducted to determine its internal consistency after a pilot study conducted outside the area of the study. A reliability coefficient of 0.78 was obtained. The researcher together with one research assistant administered the instrument to the respondents manually. A total of 50 questionnaires were administered but only 43 were retrieved. The data collected were analyzed using mean, standard deviation and regression statistics. The finding of the study among others revealed that business education lecturers have accepted to use accounting, marketing and OTM software applications for instructions. The study therefore recommended among others that there is need proper utilization of these software applications among the lecturers for effective instructional delivery.